The Impact of Gas Flaring On Man and His Environment and the Way Out - Kwame Sekyi, A. (International Journal of Engineering and Management Sciences, 2017)
The nature of flaring processes has created a severe impact on man and the environment. Massive environmental degradation as a result of flaring activities has led to fluctuations in climate as well as depletion of the vegetation cover through acid rain. Findings have been made on some harmful gases released into the atmosphere that have effects on the environment and also on man. In order to control these effects by ensuring a clean atmosphere and environment, a new flaring model (DanMat flaring model) has been suggested. The model uses smoldering mechanism to reduce the amount of heat released into the atmosphere during conventional flaring by 60%. It also uses scavengers to oxidize harmful gas produced during flaring activities into less harmful ones. With this model one can flare gas without polluting the environment since it reduces the emissions of harmful gases during flaring.